Multi-Configuration Styles of Structured Data Mashup using SDXMapping - Hardaha, Prakash Narayan; Singh, Shailendra (International Journal of Computer Sciences and Engineering, 2025)
The structured data mashup is the special kind of data mashup which deals with well structured data throughout the mashup development process. This paper highlights mashup development life cycle and the roles of IT developers as well as end users in various steps of mashup development. The pre-mashup configuration is the essential process of the any data mashup development that creates mashup module consisting of data module, service module, mapping module and UI module. In this work, we have explored mapping module called SDXMapping to design multi-configuration styles of structured data mashup, which will not only help the mashup developers but also the end users to develop the data mashup as per the situational need